The Role of Oxidative and Nitrosative Stress in Migraine Patients - Mahmood, Lana Othman; Abdoulrahman, Kamaran (Iraqi Journal of Science, 2024)
This research aimed to explore the potential involvement of oxidative stress in the onset of migraines. The primary objective was to assess the concentrations of malondialdehyde (MDA), which serves as an indicator of oxidative stress, as well as nitric oxide (NO), a marker for nitrosative stress, and asymmetric dimethylarginine (ADMA), an indicator of endothelial dysfunction. Ninety (90) participants were recruited in this research work from the neurology department's outpatient headache clinic at Al Jumhury Teaching Hospital in Erbil city, the study consisted of (60) patients and (30) as controls. In the migraine group, there were (45) females and (15) males, while the control group was comprised of (20) females and (10) males with age and sex matching. The study was granted ethical approval by the Human Research Ethics Committee (HREC) at the Department of Biology, College of Science, Salahaddin University-Erbil, on February 6th, 2022.The study showed that the migraine patients had significantly greater levels of MDA, NO and ADMA than the control group. Additionally, the number of headache days experienced per month by migraine patients was positively correlated with the serum concentrations of MDA, NO, and ADMA. Specifically, as the frequency of monthly headache days increased, levels of the oxidative stress markers MDA and NO, as well as the endothelial dysfunction marker ADMA, also tended to be higher.